Intact mangrove root electrodes for desalination. Issue 9 (11th February 2019) - Wood, Adam R.; Garg, Raghav; Justus, Kyle; Cohen-Karni, Tzahi; LeDuc, Philip; Russell, Alan J.
Abstract : Biological adaptation in mangrove root enables freestanding carbonized architecture to be used as a highly permeable flow-through capacitive deionization electrode. Abstract : Through the benefit of billions of years of evolution, biology has developed tremendous strategies on how to co-exist in high salinity and water scarce environments. Biologically-inspired abiotic systems are becoming a central pillar in how we respond to critical grand challenges that accompany exponential population growth, uncontrolled climate change and the harsh reality that 96.5% of the water on the planet is saltwater. One fascinating biologic adaptation to saltwater is the growth of mangrove trees in brackish swamps and along the coasts. Through a process of salt exclusion, the mangrove maintains a near freshwater flow from roots to leaves to survive. One abiotic approach to water desalination is capacitive deionization, which aims to desalinate low-salinity water sources at energy costs below current technologies, such as reverse osmosis and thermal distillation. In this work, we use one-step carbonization of a plant with developed aerenchyma tissue to enable highly-permeable, freestanding flow-through capacitive deionization electrodes. We show that carbonized aerenchyma from red mangrove roots reduces the resistance to water flow through electrodes by 65-fold relative to carbonized common woody biomass. We then demonstrate the practical use of the intact carbonized red mangrove roots as electrodes in a flow-through capacitive deionization system. These findings have implications in a range of fields including water desalination, bioinspired materials, and plant functionality.